1992
DOI: 10.1039/c39920000923
|View full text |Cite
|
Sign up to set email alerts
|

Stable aqueous dispersions of polyaniline

Abstract: Relatively concentrated stable aqueous dispersions o f polyaniline containing uniform spherical particles have been prepared for the first time using a underivatised poly(viny1 alcohol coacetate) as a steric stabilizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 3 publications
2
30
0
Order By: Relevance
“…On the contrary, Gospodinova et al 19 and others 20 -22 claimed successful dispersions using PVA due to efficient grafting of PVA on to the PANI particles. To overcome the problem of low adsorption of conventional stabilizers, Tadros et al 20 used tailor-made stabilizers-which could undergo graft copolymerization with ANI and thus get anchored on PANI particles to assist stable dispersion.…”
Section: Water Dispersibility Of the Pani-mmt Nanocompositesmentioning
confidence: 99%
“…On the contrary, Gospodinova et al 19 and others 20 -22 claimed successful dispersions using PVA due to efficient grafting of PVA on to the PANI particles. To overcome the problem of low adsorption of conventional stabilizers, Tadros et al 20 used tailor-made stabilizers-which could undergo graft copolymerization with ANI and thus get anchored on PANI particles to assist stable dispersion.…”
Section: Water Dispersibility Of the Pani-mmt Nanocompositesmentioning
confidence: 99%
“…et al (2011) and Sathiyanarayanan, S. et al (2007), sensors, Huyen, D.N. et al (2011), and other conductivity applications, Gospodinova, N. et al (1992), Bajpayee A.K. et al (2008), Bhadra, J. an Sarkar, D. (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Properties of Polyaniline as conducting polymer can be enhanced when it is formed as a composite materialwith Poly vinyl alcohol (PVA). Gospodinova et al (1992)reported the synthesis and whereas Bajpayee A.K. et al (2008) have discussed characterizations of a stable PANI-________________ *Corresponding author: +96893895339; E-mail address: sri_anupam2003@yahoo.co.in PVA dispersion in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the preparation of IPN of PANI with water soluble polymers like poly(vinyl alcohol) (PVA), poly(methoxy cellulose) and poly(ethylene oxide) etc. as matrix materials have been also reported in the literature [17].…”
Section: Introductionmentioning
confidence: 78%